Neuromuscular profile of elite male and female judokas with assessment using tensiomyography - Monteiro, L.; Massuca, L. (1st scientific and professional conference on judo "Applicable research in judo" - Book of abstracts, 2015)
The aim of this study is to assess the contractile properties and the lateral symmetry percentages of muscles: Biceps Brachial, Triceps Brachial, Pectoralis Major and Latissimus Dorsi of elite men and women judokas, reach the balance agonist/antagonist of arms and determine the gender influence and the specific training in the assessed parameters.